An Underappreciated and Prolonged Drug Interaction Leads to Ineffective Anticoagulation. Issue 2 (February 2019) - Rogers, Kelly C.; Neu, Daniel W.; Jaeger, Melanie C.; Shah, Rahman; Finks, Shannon W.
Abstract : Abstract: A poorly understood significant drug–drug interaction compounded by ineffective communication among providers at times of care transition most likely contributed to multiple thromboembolic events in an 81-year-old patient. Increased awareness of drug interactions with direct oral anticoagulants (DOACs), as well as improved communication among inpatient and outpatient providers at the time of discharge is essential in maximizing efficacy and safety outcomes in patients requiring chronic anticoagulation. When rifampin is coadministered with apixaban, a reduction in apixaban exposure results in decreased efficacy and increased risk for thromboembolic events. The delayed effect of rifampin deinduction should be considered with regard to potential drug interactions even after its discontinuation. Equally as important, patients with multiple comorbidities and polypharmacy are at significant risk from adverse drug events during the transition from hospital to home. All efforts to improve continuity of care at times of transition, including medication reconciliation, prompt delivery of discharge summaries to outpatient providers, effective communication among providers, and patient education are components of a best practices model that has the potential to lower costs, improve medication adherence, decrease adverse drug events, and reduce hospital readmissions. Abstract : Certain medications are known to increase or initiate enzyme activity, a process otherwise referred to as induction. In some cases, enzymatic induction may continue despite withdrawal of the offending drug for a prolonged period. This phenomenon, referred to as deinduction, is the timeframe required for enzymatic induction to wear off. This onset and offset of enzymatic activity can cause complications with concomitantly administered medications, especially during the deinduction phase if the drug is no longer being prescribed and the interaction is unrecognized.